2016
DOI: 10.1080/13607863.2016.1186150
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the geriatric mental health workforce through utilization of non-licensed providers

Abstract: Objectives The rapidly growing older adult population in the United States is poised to overwhelm the geriatric mental healthcare workforce. We evaluate several policy and practice strategies for bolstering the geriatric mental healthcare workforce and describe the costs and other considerations of implementing one approach. Method Narrative overview of the literature and policy retrieved from searches of databases, hand searches, and authoritative texts. We identified three proposed strategies to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As trainees rotate through these clinics that model interprofessional collaborative practice and team-based care, we expect to see improved uptake of processes that expand capacity through more effective teamwork. Team-based care that includes a variety of disciplines working to the top of their scope of practice and with expanded geriatric competency can achieve improved care of older adults without higher costs [17]. Furthermore, we believe that with the current structure of Medicare reimbursement, mentored comprehensive geriatric assessment is possible within primary care practices.…”
Section: Discussionmentioning
confidence: 99%
“…As trainees rotate through these clinics that model interprofessional collaborative practice and team-based care, we expect to see improved uptake of processes that expand capacity through more effective teamwork. Team-based care that includes a variety of disciplines working to the top of their scope of practice and with expanded geriatric competency can achieve improved care of older adults without higher costs [17]. Furthermore, we believe that with the current structure of Medicare reimbursement, mentored comprehensive geriatric assessment is possible within primary care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that treatment by these supervised but non-licensed providers is equally effective at improving depressive symptomatology, often with substantial cost savings. 183 , 184 A major opportunity to engage the non-physician workforce exists in long-term care facilities and age-restricted and retirement communities. Although 35% of residents in such facilities experience depressive symptoms, 50 facility staff are often untrained in identifying and managing these symptoms.…”
Section: Opportunities and Recommendations For Promoting Mental Healt...mentioning
confidence: 99%
“…The nursing and allied health workforce is more racially and ethnically diverse than that of physicians, so increased engagement with staff may provide older adults a higher degree of culturally and linguistically competent care. 184 …”
Section: Opportunities and Recommendations For Promoting Mental Healt...mentioning
confidence: 99%
“…Counselors are providing home-based services to older adults in much the same way that services are provided to children and families. In-home counseling that is delivered through an integrated team consisting of case managers, physicians, occupational and physical therapists, and others, has proven to be successful in improving outcomes and reducing the cost of care (Kunik et al, 2017). Clinical mental health counselors now are working in arenas that traditionally have been staffed by social workers.…”
Section: Services To Older Adultsmentioning
confidence: 99%